Safety and Effectiveness of Pulsed Field Ablation to Treat Atrial Fibrillation: One-Year Outcomes From the MANIFEST-PF Registry - Turagam, Mohit K; Neuzil, Petr; Schmidt, Boris; Reichlin, Tobias; Neven, Kars; Metzner, Andreas; Hansen, Jim; Blaauw, Yuri; Maury, Philippe; Arentz, Thomas; Sommer, Philipp; Anic, Ante; et al. (Circulation (New York, N.Y.), 2023)
Pulsed field ablation is a novel nonthermal cardiac ablation modality using ultra-rapid electrical pulses to cause cell death by a mechanism of irreversible electroporation. Unlike the traditional ablation energy sources, pulsed field ablation has demonstrated significant preferentiality to myocardial tissue ablation, and thus avoids certain thermally mediated complications. However, its safety and effectiveness remain unknown in usual clinical care. MANIFEST-PF (Multi-National Survey on the Methods, Efficacy, and Safety on the Post-Approval Clinical Use of Pulsed Field Ablation) is a retrospective, multinational, patient-level registry wherein patients at each center were prospectively included in their respective center registries. The registry included all patients undergoing postapproval treatment with a multielectrode 5-spline pulsed field ablation catheter to treat atrial fibrillation (AF) between March 1, 2021, and May 30, 2022. The primary effectiveness outcome was freedom from clinical documented atrial arrhythmia (AF/atrial flutter/atrial tachycardia) of ≥30 seconds on the basis of electrocardiographic data after a 3-month blanking period (on or off antiarrhythmic drugs). Safety outcomes included the composite of acute (<7 days postprocedure) and latent (>7 days) major adverse events. At 24 European centers (77 operators) pulsed field ablation was performed in 1568 patients with AF: age 64.5±11.5 years, female 35%, paroxysmal/persistent AF 65%/32%, CHA DS -VASc 2.2±1.6, median left ventricular ejection fraction 60%, and left atrial diameter 42 mm. Pulmonary vein isolation was achieved in 99.2% of patients. After a median (interquartile range) follow-up of 367 (289-421) days, the 1-year Kaplan-Meier estimate for freedom from atrial arrhythmia was 78.1% (95% CI, 76.0%-80.0%); clinical effectiveness was more common in patients with paroxysmal AF versus persistent AF (81.6% versus 71.5%; =0.001). Acute major adverse events occurred in 1.9% of patients. In this large observational registry of the postapproval clinical use of pulsed field technology to treat AF, catheter ablation using pulsed field energy was clinically effective in 78% of patients with AF.